Analisis Struktur Kepemilikian Terhadap Kinerja Keuangan dengan Struktur Modal, Manajemen Laba, Karakteristik Perusahaan Sebagai Variabel Intervening Pada Perusahaan Jasa Yang Terdaftar di Bursa Efek Indonesia - Christine Cicilia Saputra; Hwihanus Hwihanus (Jurnal Kendali Akuntansi, 2024)
This study aims to analyze the effect of ownership structure on financial performance in service companies by considering the role of capital structure, earnings management, and company characteristics as intervening variables. The data used in this study comes from the financial statements of service companies listed on the Indonesia Stock Exchange during a certain period. The analysis tool used is SmartPls. The results showed that ownership structure has a significant influence on the company's financial performance. In addition, capital structure is also found to have an important role as an intervening variable in the relationship. These findings provide important insights for managers and stakeholders in optimizing ownership and capital structure to improve the financial performance of the firm.